Role of molecular evolution in respiratory syncytial virus antigenic proteins during annual epidemics in South Africa - Agenbach., Elizabeth. (My University, 2004)
Respiratory syncytial virus (RSV) is a major cause of pneumonia in children worldwide and there is currently no vaccine available. Molecular analysis of annual RSV epidemics in Soweto (1997 to 2000), revealed co-circulation and displacement of dominant genotypes. However in 1999 to 2000, one genotype GA2, predominated. To further elucidate the molecular epidemiology of RSV in South Africa the 2001 RSV epidemic in Soweto was characterised. Phylogenetic analysis of the G-protein revealed subtype B dominance (89%). Sequences clustered in genotypes GA2, GA5, SAA1, GB3, SAB1 and SAB3. SAB3 dominanted (69%) followed by SAB1 (18%), thereby displacing GA2, which dominated the previous two seasons. Evidence of positive selection may account for the genetic variability observed and may contribute to the reestablishment of annual epidemics. To investigate if this influences evolution of other RSV antigenic proteins the F-protein of South African genotypes was characterised. Most amino acid differences identified within known neutralising and CTL epitopes were conserved within subtype A, and although this does not suggest immune selection these epitopes may not be recognised efficiently by antibodies or CTL specific to subtype B viruses
A Thesis submitted to the Faculty of Health Sciences University of the Witwatersrand, Johannesburg In fulfilment of the requirements for the Degree of Master of Science Johannesburg 2004
Keywords: Child; Respiratory Syncytial Viruses; Pneumonia